Manoeuvring simulations in adverse weather conditions with the effects of propeller and rudder emergence taken into account. (1st February 2020) - Aung, Myo Zin; Umeda, Naoya
Abstract: Manoeuvring simulations in realistic sea conditions, i.e. in wind and waves, have recently got the attention due to several reasons such as stringent EEDI regulations and associated minimum power guidelines, optimization of ship design with respect to the real operating conditions, assessment of safety performance in extreme weather conditions etc. In this paper, a modular simulation model for manoeuvring in adverse weather conditions is proposed. The effects of propeller and rudder emergences on ship behaviour and propulsion engine's dynamics are also taken into account by integrating the first order 6DOF ship motions into the manoeuvring model. The engine's load limits are also explicitly considered using the fuel limiter inside the governor. Various manoeuvring simulations are investigated by using the different initial conditions, propulsion engines and environmental conditions. The difference in the initial forward speeds of time-domain simulations is found to have the significant effects on ship trajectories although the final equilibrium ship speeds are the same. The choice of engine's SMCR with higher light running margin (LRM) is found to have the substantial advantageous over ship speed and safety in adverse weather conditions but with some compromises in calm water ship speed, calm water SFOC and EEDI values. Highlights: A simulation model for manoeuvring in adverse weather conditions which also considers the effect of propeller and rudder emergence and subsequent effects on the engine-propeller dynamics in time domain is proposed. The engine's load limits such as speed limit, power limit, torque limit, torque/speed limit etc. are explicitly considered inside the engine speed controller (governor). Various manoeuvring simulations are investigated by using the different initial conditions, environmental conditions and propulsion engines. The effects of propeller and rudder emergences, the advantageous and disadvantageous of choosing the engine's SMCR with higher LRM (Light Running Margin) in adverse weather conditions are discussed.